Enhancing Surveillance : Interconnectedness and Clusters. (Policy Papers; Policy Paper ;, 2012)
This paper provides additional detail for the framework discussed in 'Enhancing Surveillance - Interconnectedness and Clusters' through theoretical and empirical analysis of linkages, including case studies of Saudi Arabia, the Asian supply chain, financial interconnectedness and cross-border policy dependence in banking, and the Sweden-Baltic connections. It also provides a detailed primer on network analysis.